La pena privativa de libertad y el principio de mínima intervención penal en las contravenciones de tránsito, en el Juzgado Penal de Guaranda, 2020. - Ulloa Toalombo, José Andrés (2022)
Traffic violations that have a custodial sentence as a sanction, is an issue that is becoming increasingly important within society, thus giving rise to these violations committed by people who drive a vehicle disregarding the rule and the objective duty of care; which causes legal conflicts that end with sanctions that can go up to the deprivation of liberty. The custodial sentence today has great relevance and at the same time has become a topic of debate, that despite being exceptional last resort, justice administrators are abusing the restrictive custodial sentence of human rights and constitutional that according to the results of this investigation causes violation of constitutional rights and principles, especially the principle of proportionality, and minimal criminal intervention. Indeed, when a person commits a traffic violation, it is true that he is going against what the law establishes, in this case the regulation is the Comprehensive Organic Criminal Code (COIP) that typifies these acts. When speaking of the principle of minimal criminal intervention, he mentions that it is the last resort to make use of the criminal sphere, although it is true that the violations are found within the COIP, however, these could be dealt with by another legal means or, in turn, establish non-custodial sanctions. In relation to the principle of proportionality, emphasis is placed between the crime and the traffic violation that, despite being completely different at the time of being tried, each of these can show that the procedure for the trial of a violation with a custodial sentence is harmful to the offender, taking into account that the sentence is immediate.